2015
DOI: 10.1109/tdmr.2015.2468587
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Degradation of Mid-Power White-Light LEDs in Saturated Moisture Conditions

Abstract: Serious silicone carbonization has been reported in mid-power white light LEDs during highly-accelerated temperature and humidity stress test (HAST), even though the junction temperature of the LED chip is much lower than the critical temperature of silicone carbonization (300 °C). This paper presents a comprehensive investigation, through which, the effects of Joule heating and phosphor self-heating has been eliminated as main failure mechanisms. As a result, the over-absorption of blue lights by silicone bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Due to lack of equipments, we could not analyze the degradation of the silicone encapsulant lead frames, and phosphors. However, our previous research already showed very good performance for these two materials [50]. As a result, it was concluded that the major degradation was the yellowing of the package housing.…”
Section: Methodsmentioning
confidence: 92%
“…Due to lack of equipments, we could not analyze the degradation of the silicone encapsulant lead frames, and phosphors. However, our previous research already showed very good performance for these two materials [50]. As a result, it was concluded that the major degradation was the yellowing of the package housing.…”
Section: Methodsmentioning
confidence: 92%
“…High power phosphor-converted white light-emitting diodes (pc-WLEDs) have been accepted as an important substitute for traditional lighting sources due to their high luminous efficiency, low power consumption, longer lifetime and their environmental friendliness [1,2]. In pc-WLEDs system, silicone or silicone-based materials are commonly used as an encapsulant due to good optical properties like high refractive index, good ultraviolet light resistance [3], and high thermal stability [4] and the resistance to discoloration at high temperature [5]. In pc-WLEDs, the silicone encapsulants are combined with phosphors to form a composite for blue light conversion and chip protection.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of white LEDs (WLEDs) available in the marked are based on the usage of a blue chip covered with YAG:Ce 3+ embedded in an epoxy resin or silicone as an encapsulant. However, heat generated from high‐power LEDs may lead to yellowing, carbonization, and browning of the encapsulant and thus change the color temperature of the WLED and decrease its luminous efficacy. Different techniques have emerged to overcome these drawbacks, among these we find approaches such as glass‐ceramics, and phosphor in glass (PIG) .…”
Section: Introductionmentioning
confidence: 99%